Pisarska podróż Ryszarda Krynickiego - Morawiec, Arkadiusz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
The metaphor of a journey arranges and explains the literary work by Ryszard Krynicki, its evolution, the presented world, and idea. The journey is one of the most important key words and motifs of Krynicki‘s poetry, and a metaphor of human destiny. The term "artistic journey", related to this work, is more than a trite metaphor. Krynicki‘s road leads from nothingness, the world without norms, values, the world of illusory existence, towards Nothingness, The Absolute. The writer should be seen as a seeker that completed a fascinating, complicated journey in pursuit of excellence, artistic, moral, and spiritual, as a man responsible for the word. Ryszard Krynicki‘s literary journey leads from chaos to cosmos, from logorea to Logos, from the fall to prospective redemption.